PERANCANGAN SISTEM INFORMASI MANAJEMEN SURAT DI SDN 1 BAYEMAN - Khoirunisak, Dewi; Ghofur, Abd (Journal of Advanced Research in Informatics, 2024)
ABSTRACT - The development of Information Technology in 2024 will increase rapidly in educational institutions and the wider community. This makes it easier for humans to do work. However, there are several agencies or institutions that still use manual systems. Bayeman 1 Elementary School is one of the educational institutions that still uses a manual system for mail management. This is less efficient and ineffective because letter numbers are often confused and the storage of letters is irregular, resulting in letters being damaged or even lost. This research aims to design a mail management information system to improve and optimize the mail processing process at SD Negeri 1 Bayemen. With this information system, it is hoped that it can help TU officers in managing letters more quickly and efficiently. ABSTRAK - Perkembangan Teknologi Informasi pada tahun 2024 meningkat pesat pada lembaga Pendidikan maupun masyarakat luas. Hal ini memudahkan manusia dalam melakukan pekerjaan. Namun ada bebrapa instansi atau lembaga yang masih menggunakan sistem manual. SD Negeri 1 Bayeman termasuk lembaga Pendidikan yang masih menggunakan sistem manual dalam manajemen surat. Hal tersebut kurang efisien dan tidak efektif karena sering terjadi nomor surat yang salah serta penyimpanan surat yang tidak teratur, sehingga surat rusak bahkan hilang. Penelitian ini bertujuan merancang sistem informasi manajemen surat untuk memperbaiki dan mengoptimalkan proses pengolahan surat pada SD Negeri 1 Bayemen. Dengan adanya sistem informasi ini, diharapkan dapat membantu petugas TU dalam manajemen surat agar menjadi lebih cepat dan efisien.